2015
DOI: 10.1128/mcb.00514-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a CTCF-Dependent Insulator on Multiple Aspects of Enhancer-Mediated Chromatin Organization

Abstract: Developmental stage-specific enhancer-promoter-insulator interactions regulate the chromatin configuration necessary for transcription at various loci and additionally for VDJ recombination at antigen receptor loci that encode immunoglobulins and T-cell receptors. To investigate these regulatory interactions, we analyzed the epigenetic landscape of the murine T-cell receptor ␤ (TCR␤) locus in the presence and absence of an ectopic CTCF-dependent enhancer-blocking insulator, H19-ICR, in genetically manipulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…The excluded PDb1-DJCb1 region is likely to escape Eb-mediated chromatin changes. Consistent with this, our 3C-qPCR analysis indicated reduced Eb-PDb1 interaction, reduced PDb1-DJCb1 chromatin accessibility (37), and a marked reduction in DJCb1 recombination (30). As predicted, Eb-based activation of PDb2 and the linked DJCb2 cluster was unaltered.…”
Section: Csupporting
confidence: 72%
See 4 more Smart Citations
“…The excluded PDb1-DJCb1 region is likely to escape Eb-mediated chromatin changes. Consistent with this, our 3C-qPCR analysis indicated reduced Eb-PDb1 interaction, reduced PDb1-DJCb1 chromatin accessibility (37), and a marked reduction in DJCb1 recombination (30). As predicted, Eb-based activation of PDb2 and the linked DJCb2 cluster was unaltered.…”
Section: Csupporting
confidence: 72%
“…This suggested that in addition to proximity, the precise relative configuration of the chromatin loop encompassing the RC and the V segments in TCR-ins was influenced by the altered CBS interactions and impacted RSS-mediated recombination. Based on functional analysis, we have earlier proposed that CTCF can both facilitate and inhibit RSS-mediated recombination (30,37). Our 3C-qPCR-based analysis of the chromatin interactions in wild-type and mutant TCRb alleles supports this contention.…”
Section: A Mutant Locus Tcr-ins 100kbsupporting
confidence: 72%
See 3 more Smart Citations